1994
DOI: 10.1002/jemt.1070280203
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the basement membrane

Abstract: The aim of this contribution is to summarize our knowledge of the morphology of the basement membrane (BM). The first step in this direction is the attempt to define this term. The BM is composed of the Lamina lucida, densa, and fibroreticularis. Subsequently, the historical development of this term is discussed. Our main interest is, of course, focused on the description of the BM-structure up to the macromolecular level and the special forms of this structure. This is supplemented by discussing its chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
66
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 197 publications
(230 reference statements)
1
66
0
5
Order By: Relevance
“…Hence, myofibroblasts could be immunohistochemically distinguished by coexpression of vimentin and a-smooth muscle actin (a-SMA) without expression of desmin or calponin. [4][5][6] Recent investigations have shown that the stromal reaction was more pronounced in Gleason pattern 3 compared to other Gleason pattern tumours. 2,3 To become invasive, prostate cancer cell must first penetrate acinar basement membrane (BM) proteins and extracellular matrix adhesive glycoproteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, myofibroblasts could be immunohistochemically distinguished by coexpression of vimentin and a-smooth muscle actin (a-SMA) without expression of desmin or calponin. [4][5][6] Recent investigations have shown that the stromal reaction was more pronounced in Gleason pattern 3 compared to other Gleason pattern tumours. 2,3 To become invasive, prostate cancer cell must first penetrate acinar basement membrane (BM) proteins and extracellular matrix adhesive glycoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…5 Structural components of the BM are laminins, type IV and type VII collagens, nidogens and proteoglycans. 6 Laminins are heterotrimeric molecules made up by one a, one b and one g chain. Until today, we know of five a-chains, three b-chains and three g-chains.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, endothelium, various types of muscle cell, lipocytes and Schwann cells are surrounded by BM. 1 Structural components of the BM are at least laminins, type IV collagens, nidogens, proteoglycans such as perlecan, fibulins as well as type VII collagen in the BMs containing lamina fibroreticularis layer. Additionally, fibronectin and tenascin are often located to the BM region, but they are not the structural components of the BMs.…”
mentioning
confidence: 99%
“…The lamina reticularis is not apparent in all tissues; however, it is well developed under multilayered epithelium. It is especially pronounced under the respiratory epithelium of large conducting airways, where it may be several microns thick (Merker, 1994). The lamina reticularis is made up of numerous collagen fibrils.…”
mentioning
confidence: 99%
“…The lamina reticularis is made up of numerous collagen fibrils. Immunohistochemical studies have shown that the collagen fibrils consist of Types I, III, V, VI, and VII collagen (Merker, 1994). The collagen fibrils are arranged as a mat of large fibers oriented along the longitudinal axis of the airway when viewed with scanning electron microscopy.…”
mentioning
confidence: 99%